Factors Influencing the Prevention of Hypertension in the Working Area of Martubung Health Center, Medan Labuhan District - Wagini Wagini; Ismail Efendy; Endang Maryanti (Journal La Medihealtico, 2023)
The objective of the study was to identify the factors that influence the prevention of hypertension in the Martubung Public Health Center's service area in the Labuhan District of Medan.The research design employed a quantitative method that was implemented through an analytical survey employing the Cross Sectional Study methodology. The cohort of this research consisted of hypertensive patients who visited as many as 712 patients. With the technique of Accidental Sampling, 88 respondents comprised the sample. The analysis of data employed univariate, bivariate, and multivariate methods.Knowledge p = 0.000, attitude p = 0.000, culture p = 0.008, diet p = 0.000, physical activity p = 0.000, and the role of health workers p = 0.001 were found to have an effect on hypertension prevention at the Martubung Public Health Center in the Medan Labuhan District. While knowledge is the most influential factor, p = 0.001 with 95% CI = 5.663-201,428 and Exp(B) = 104,118.This study concludes that knowledge, attitude, culture, diet, physical activity, and the function of health employees influence the prevention of hypertension at the Martubung Public Health Center in the Labuhan District of Medan. It is recommended that the Martbung Health Center optimize the counseling and dissemination of health information related to health promotion, general and special protection, and regular health checks in accordance with the program currently being implemented by the government, so that the community can actively participate in realizing healthy behavior, including the management of noncommunicable diseases.